2007
DOI: 10.4081/ijas.2007.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of dietary biotin on the performance and bone structure of broilers

Abstract: We evaluated the effects of different levels of biotin on broilers performances and bone growth. Biotin was added at concentrations of 100, 200, 300, 400, 500 μg/Kg to a corn and soybean diet for yellow skin broiler production during the whole production cycle. Biotin at dosages of 200, 300, 400 μg/Kg increased growth rate, and, regardless of dosage, feed conversion rate in the second and third period of growth. Femur and tibiotarsus volume was slightly reduced while the bone mineral content of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
7
0
4
Order By: Relevance
“…It is clearly observed that pullets fed diet supplemented with biotin at a level of 150 µg/ kg and 100 µg/ kg recorded the higher averages of plasma calcium and inorganic phosphorus levels (6.97 and 3.79 mg/ dL, respectively) compared with the other biotin levels and control group. This result agrees with those reported by Afro et al, (2007) who stated that, the serum calcium and phosphorus levels were significantly higher in of birds fed on diet supplemented with biotin at a level of 300 μg/ kg diet compared to control group. Plasma calcium and inorganic phosphorus has significant varied due to the different periods of estimation, the higher plasma calcium and inorganic phosphorus (6.74 and 3.55 mg/ dL, respectively) were found at the end of experiment.…”
Section: Absolute and Relative Weights Of Egg Components And Shell Thsupporting
confidence: 93%
“…It is clearly observed that pullets fed diet supplemented with biotin at a level of 150 µg/ kg and 100 µg/ kg recorded the higher averages of plasma calcium and inorganic phosphorus levels (6.97 and 3.79 mg/ dL, respectively) compared with the other biotin levels and control group. This result agrees with those reported by Afro et al, (2007) who stated that, the serum calcium and phosphorus levels were significantly higher in of birds fed on diet supplemented with biotin at a level of 300 μg/ kg diet compared to control group. Plasma calcium and inorganic phosphorus has significant varied due to the different periods of estimation, the higher plasma calcium and inorganic phosphorus (6.74 and 3.55 mg/ dL, respectively) were found at the end of experiment.…”
Section: Absolute and Relative Weights Of Egg Components And Shell Thsupporting
confidence: 93%
“…Choline is a well-known lipotropic factor responsible for the mobilisation of liver fat in the form of lipoproteins toward extra-hepatic tissues where they may be metabolised or deposited [ 42 , 43 ]. As a result, the excess fat energy gets diverted towards muscle protein accretion rather than body fat synthesis, resulting in better growth, improved FCR and lower lipid content in liver, abdomen, and carcass [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tibia widths of male and females broilers at 32 and 48 days of age were changed between 6.20-6-50 mm and between 8.44-9.07 mm (Yalcin et al 2001). In a study by Quarantelli et al (2007), lengths of femur bone at 21, 41 and 61 days of age as 51. 40-54.57mm, 75.50-79.87mm and 90.50-97.37mm, but lengths of tibia bone as 72.47-96.0mm, 107.5-114.5mm and 132.43-140.83 mm were determines, respectively.…”
Section: Findings and Discussionmentioning
confidence: 89%